Omics insights into Bacillus velezensis LMY3-5 defense against Botryosphaeria dothidea in kiwifruit - Chunguang Ren; Yu Liu; Wenwen Su; Zhengcheng Han; Di Wu; Weijie Li (Frontiers in Microbiology)
Botryosphaeria dothidea is the main cause of soft rot in kiwifruit, significantly reducing both yield and quality. While chemical treatments are commonly used, their effectiveness is limited and they may pose environmental risks. As a result, biological control using Bacillus species has emerged as a promising alternative. In this study, we explored the antifungal mechanism of the biocontrol strain Bacillus velezensis LMY3-5 against kiwifruit soft rot through integrated genomic and transcriptomic analyses. In terms of antagonistic activity: B. velezensis LMY3-5 exhibits strong antagonism against B. dothidea, the causal agent of kiwifruit soft rot, showing a 70.44% biocontrol efficacy in inoculation tests. In terms of genomic features: genome 4.03 Mb circular chromosome with 46.5% GC content. Eight antimicrobial BGCs were identified, including those for surfactin, fengycin, bacillaene, bacillibactin, and others, explaining its biocontrol potential. In terms of transcriptomic insights: during coculture with B. dothidea, 114 DEGs (31 upregulated, 93 downregulated) were detected. Downregulated: flagellar assembly and chemotaxis genes (suggesting reduced motility during antagonism). Upregulated: genes linked to fengycin, siderophores, and lysozyme production, critical for antifungal activity. In terms of mechanism and implications lipopeptides (e.g., fengycin) and siderophores are key in inhibiting fungal growth. Findings support LMY3-5’s potential as a biocontrol agent for plant protection against B. dothidea. The main conclusion of this study is LMY3-5 combats B. dothidea via antimicrobial metabolites, with genomics and transcriptomics revealing its molecular basis for biocontrol. This strain holds promise for sustainable plant disease management. This may provide a theoretical basis for the potential application of B. velezensis LMY3-5 in the field of plant protection in the future.